THE ARABIC LANGUAGE: ITS RELEVANCE TO NIGERIAN DEVELOPMENT - Ayuba, Mahmud Adesina (European Scientific Journal, ESJ, 2012)
This is an attempt to give an expository analysis of the relevance of Arabic, which by virtue of Islam, had established itself in Nigeria as the language of administration, literacy, education, history and legislation before the arrival of colonial masters, to Nigerian development. Thus, the cut and thrust of this paper is the examination of the role of Arabic language in the development of Nigeria. Methodologies employed in this paper are historical and sociological approaches. The paper discovered that with the spread of Islam in Nigeria, learning of Arabic language through the acquisition of Islamic education commenced. It was also observed that Arabic language had contributed immensely to the development of Nigeria as a nation in the past and that its neglect would not augur well for Nigerian development. The paper, therefore, argues that Arabic has a lot to offer in the upliftment of the country, especially in the areas of religion, education, economy, socio-psychology, diplomacy and security. Finally, the paper affirms that the significance of Arabic as a language transcends the religious sphere and concludes on the note that Arabic should be given its prime place and be allowed to contribute its own quota to the development of Nigeria.